WebTOP: web-based interactive 3D optics and waves' simulations. (20th April 2005) - Mzoughi, Taha; Foley, John T.; Herring, S. Davis; Morris, Matt; , Ben Wyser
WebTOP is a three-dimensional, interactive computer graphics system developed at the Mississippi State University to help students learn about optics and waves. It has been used to help teach undergraduate introductory physics and upper-level optics classes. WebTOP is designed to be flexible, allowing faculty and students to use it in a variety of ways. It can be used for homework, classroom demonstrations, laboratories, and online tutorials. Currently, it comprises sixteen modules spanning eight different subject areas. The subject areas are waves, geometrical optics, reflection and refraction, polarisation, interference, diffraction, lasers, and scattering. This paper provides an overview of WebTOP, a description of each of the current modules, as well as outline of WebTOP's use for teaching and learning.